Korelasi antara Modification of Diet in Renal Disease (MDRD) dan Cystatin C Serum pada Usia 40–70 Tahun - Jason Jus; Ronald Irwanto; Pusparini (Majalah kedokteran Bandung, 2016)
Reporting of the estimated glomerular filtration rate (GFR) in every creatinine test is suggested, despite the fact that every laboratory reports it in their result. Modification of Diet in Renal Disease (MDRD) is a formula that is used to estimate the GFR using serum creatinine. Serum cystatin C is a relatively new test and superior for assessing kidney functions. The purpose of this study was to show the correlation between MDRD and serum cystatin C. A cross-sectional study was conducted using secondary data from 260 subjects, aged 40–70 years old to assess serum creatinine and serum cystatin C at a private laboratory in West Jakarta, during the period of January 2013–September 2014. The result of the study showed that the mean age of subjects was 55.7+7.8 years old, the mean serum cystatin C level was 0.99 + 0.6 mg/L, and the mean MDRD was 80.24±28.1 mL/min/1.73 m2. Pearson correlation analysis showed a negative correlation between MDRD and serum cystatin C with r = -0.767 and p =0.001. In conclusion, higher MDRD presents lower cystatin C serum; hence, MDRD can be used as an alternative renal function test when serum cystatin C is not available. [